Causality Analysis between Stock Market Indices - Paweł Sekuła (Nauki o Finansach)
The paper examines relationships between selected stock market indices in Western Europe, Central Europe, and the United States. The study focuses on two periods, from January 1998 to August 2006 and from September 2006 to December 2016. The first one includes stock quotes from before the financial crisis while the second one covers the crisis and changes in the economic situation in post-crisis years. Relationships between stock market indices in developed economies were more frequent and durable than in Central Europe, although they were subject to changes. In our investigation into Granger causality relationships we observed changes in these relationships and in their direction for stock markets in Central Europe, while bidirectional relationships between indices in developed economies remained stable over time. Changes in relationships between indices, in particular long- -term interdependences, may result from the impact of the 2008 financial crisis. The increased number of causality relationships for the markets in Central Europe may testify to the advancing integration of the EU common market.(original abstract)